Uji aktivitas antioksidan ekstrak etanol, etil asetat, dan n-heksan akar kayu manis hutan (Cinnamomum Iners) Reinw. EX Nees & T. Nees Blume dengan Metode DPPH - Faisal , Hendri; Andry, Muhammad; Winata, Hanafis Sastra; Panjaitan, Yuli Cahyani (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background: Forest cinnamon (Cinnamomum iners) Reinw. Ex Ness & T. Ness Blume has been used traditionally to kill microorganisms, diarrhea and dismonere. Forest cinnamon contains compounds that act as antioxidants, including flavonoids, alkaloids, tannins, and phenolics. The antioxidant effects of vitamin C, E, carotene, and phenolic compounds (especially polyphenols and flavonoids) can potentially reduce the risk of degenerative diseases. Objective: compounds from forest cinnamon roots and determine the yield based on the level of polarity to DPPH with the IC50 value. Method; eksperimental di laboratorium yaitu melakukan percobaan terhadap aktivitas antioksidan dari ekstrak akar kayu manis hutan (Cinnamomum Iners) dengan Metode DPPH (1,1- difenil -2 pikrihidrazil). Penelitian meliputi pengumpulan akar kayu manis hutan, pembuatan ekstrak akar kayu manis hutan, uji skrining fitokimia terhadap akar kayu manis hutan, dan uji antioksidan dari ekstrak akar kayu manis hutan dengan Metode penangkalan radikal bebas DPPH (1,1-difenil –2 pikrihidrazil) menggunakan alat spektrofotometer. Results: The antioxidant activity of the ethanol solvent showed a very strong category, the ethyl acetate solvent showed medium category activity, and the n-hexane solvent showed weak category antioxidant activity. The average IC50 value of ethanol extract was 9.1 ppm, ethyl acetate extract was 77.58 ppm, and n-hexane extract was 185.08. Conclusion: forest cinnamon root (Cinnamomum Iners) Reinw. Ex Ness & T. Ness Blume has strong antioxidant activity in ethanol solvents.